Teaching Strategies in EFL Hybrid Classroom : A Case Study in a Junior High School - Farida Hamid; Dian Rinawati; Muhamad Abdul Fatah Silmi Mahrudin; Nida Husna; Didin Nuruddin Hidayat; Andi Miftahul Maulidil Mursyid (Institut Agama Islam Negeri Palopo, 2022)
This study aimed to find out which teaching strategies found in the EFL learning during this pandemic situation, where hybrid classrooms has begun to flourish as one of the strategies in learning process. This case study research with qualitative approach was conducted at one private Junior High School in academic year 2021/2022 where the subjects were 3 English teachers of grade 7-9. In this study, the data was compiled by doing direct observation as well as interview session with the participants. The data were analyzed by using the Miles and Hubberman flow model was used to analyzed the data. The findings showed that the EFL teaching strategies during this Hybrid class were mostly conducted using discussion, co-operative learning, small group discussion and some direct instructions. Even though no totally fully used, the teachers emphasize the use of English as a daily conversation in the school environment, including language learning in the classroom, both in online and offline sessions.